Compositional characteristics and nutritional quality of indigenous fruit of artocarpus odoratissimus blanco - Halifah Afiza Ismail; Shiamala Devi Ramaiya; Muta Harah Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2023)
Artocarpus odoratissimus, locally known as terap, is native to Borneo and holds great potential for providing nutrition and income to rural communities. The fruit's flesh is consumed raw, while the seeds are typically steamed and used in local dishes. The by-products, such as the pedicel and peel, often go to waste. This indigenous species has yet to be fully explored for its nutritional and phytochemical properties. Hence, the present study aims to evaluate the nutritional compositions and phytochemical properties of A. odoratissimus fruit. The nutritional and phytochemical properties of A. odoratissimus vary across its parts. The edible flesh and seeds exhibited higher carbohydrate content at 12.16±1.01% and 9.96±0.76%, respectively. Seeds possessed significantly higher crude protein (21.89±0.54%) and fat (18.23±0.20%). In contrast, the non-edible parts of the peel (5.57±0.11%) and pedicel (5.79±0.41%) exhibit considerably greater ash content than their edible counterparts in the flesh (3.87±0.42%) and seeds (0.62±0.29%). Potassium (905.61±18.89 to 2001.51±13.00 mg 100 g-1) was the most abundant in A. odoratissimus fruits, followed by calcium (578.30±7.00 to 1300.97±23.51 mg 100 g-1). The flesh is primarily composed of non-reducing sugars, including fructose (26.70±0.70 g 100 g-1) and glucose (25.38±0.45 g 100 g-1), with a notable amount of vitamin B1 (11.07±0.31 mg 100 g-1). The seed oil contains essential fatty acids, with a significant proportion of unsaturated fatty acids (57.10%), mainly nervonic acid (45.32%). The pedicel, often considered a by-product, exhibits relatively high levels of phytochemical properties in comparison to the edible portions. The current findings support the ethnobotanical uses of A. odoratissimus by local communities, underscoring its growing importance in the nutraceutical and pharmaceutical industries.